Os ideários pós-modernos no mundo do trabalho: implicações para o campo de trabalho da educação física - Gomes, Gabriel Vielmo (2022)
The present research has as its central theme the world of work in physical education, from an epistemological approach. We raise as a research problem the following question: how are the metamorphoses promoted by postmodern ideas and the implications for the area of physical education presented in the world of work? Essentially, we intend to: analyze how postmodern ideas are presented in the world of work and the implications for the field of physical education work; to verify the consequences of the changes in the world of work in the elaboration of new educational policies in the area; Analyze the consequences of changes in the world of work in the context of formal and/or self-employed in the field of Physical Education; to investigate how the scientific knowledge of the area is treated/recognized in the contemporary context. We assume as a hypothesis: the phenomenon of uberization as the category that expresses the ideals of postmodernity, which has been promoting intense changes in the world of work, and, therefore, in the specificity of physical education, as well as in its specific training and in the scientific knowledge required in the current context of contemporary society. As a research method, we resort to historical materialism – dialectical, thus configuring the study, in a research with a critical-dialectical approach. Our investigative process is characterized by being theoretically based from the classical literature of the central theme of the study, elaborating mediations and syntheses with the specificity of physical education. We used as methodological categories: totality, contradiction and mediation, and as content categories: world of work; uberization; postmodernity; PE; initial training educational policies. As a result of this research, we found that the job market in Physical Education has moved in a similar way with the propositions inherent to the Toyotist model (when referring to the rationality/form of contemporary work), as well as the implications arising from the realization of Industry 4.0 (when it relates to the instruments/work system). In this way, it is possible to verify the practice in the specific market, situations that aim to accentuate working conditions (polyvalence, increased workload, etc.), at the same time that it promotes the weakening of work relationships (outsourcing, contracts temporary jobs, pejotization, among other ways), associating, still, the reality of digital platforms/applications that intensify, for example, the intermittent/uberized work in a context of structural crisis of the capitalist production system. The final consideration turns to realize that in the current socio-historical moment the Physical Education job market assumes the character of employing the neoliberal postmodern perspective that, unfolds in individualized and fragmented visions of reality, implying to the work contemporary the realization of an entrepreneurial vision, expressed by the fetishized perception of the “boss of himself”, widely used by the digital/computational labor scenario that makes massive use of these technologies, capillarizing the “phenomenon of uberization”, where labor has assumed, its relationship and dependence on technology.